The public health consequences of sport specialization - Bell, D. R.; DiStefano, L.; Pandya, N. K.; McGuine, T. A. (Journal of Athletic Training, 2019)
Sport specialization was thought to affect a relatively small number of elite athletes, but it is now a common practice in youth sport culture. Recent research in the field of sport specialization has led to a better understanding of the influence this issue is having on youth (ie, younger than 19 years of age) today. This review focuses on sport specialization from a public health perspective to elucidate the effect that this practice is having within the United States. The specific goals of this review are to describe (1) the prevalence of sport specialization and the factors that may affect the decision to specialize, (2) the costs of youth sport-related injuries in the context of sport specialization, (3) the financial costs that sport specialization has for families, and (4) how sport specialization may be affecting physical literacy.